Identification of behavioral patterns in young science communicators in Mexico. - Mejía López, Damaris Yunuen; Martínez Mejía, Daira (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2026)
OBJECTIVE: To identify behavioral patterns in young science communicators in Mexico.MATERIAL AND METHOD: This is a descriptive study with a non-experimental, cross-sectional design. The non-probabilistic sample is composed of a total of 25 young science communicators nationwide. The research period was September 2025. The Type A or B Behavior Pattern instrument was used; it has validity and reliability, with a Cronbach’s Alpha coefficient of 0.7933, and is composed of four dimensions and 78 items, developed using Thurstone’s interval scale.RESULTS: It was possible to identify that participants in the selected sample show a clear belonging to the behavioral pattern identified as Type A behavior.CONCLUSIONS: The importance of the present research is that it contributes to the body of knowledge through the findings that indicate the existence of a behavioral pattern known as Type A in young people who carry out science dissemination processes in Mexico and, with this, it is possible to make suggestions to the participants so that they take effective actions for its control, thereby contributing to improving the quality of life of its members.
Keywords: behavioral pattern; type A behavior; type B behavior; science communicator.